1996
DOI: 10.1093/ageing/25.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Alterations of Acute-phase Proteins in Healthy Elderly Persons

Abstract: To assess acute-phase proteins in relation to ageing, we measured serum concentrations of C-reactive protein of AGP in 131 healthy elderly individuals (aged >/= 65 years) living independently in the community, and 47 healthy younger individuals. Concentrations of CRP in the older persons (median = 3.0 microg/ml) were significantly greater than in the younger group (median = 0.9 microg/ml, p = 0. 0003). Concentrations of SAA and AGP were similar in the two groups, but AGP glycosylation forms with reduced bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
78
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 30 publications
10
78
1
1
Order By: Relevance
“…Serum Amyloid A (Saa) is a component of a group of major acute phase proteins, and its expression increases in response to infection or systemic inflammation. In agreement with previous works (Vranckx et al 1995;Ballou et al 1996), the present study found that the expression levels of this gene family (consisting, in mouse, of three active genes, Saa1, Saa2, Saa3) were 9-to 55-fold higher in old mice compared to young animals. These results suggest that inflammation is a component of aging process in the liver, according to the concept of the existence in aged animals of a state of chronic inflammation in the absence of Bstressors.^Genes involved in immune response were also up-regulated in aged liver; particularly striking was the 40-fold increase in the expression of lipocalin 2, a novel autocrine and paracrine adipokine, which acts as an antagonist of inflammatory molecules.…”
Section: Resultssupporting
confidence: 93%
“…Serum Amyloid A (Saa) is a component of a group of major acute phase proteins, and its expression increases in response to infection or systemic inflammation. In agreement with previous works (Vranckx et al 1995;Ballou et al 1996), the present study found that the expression levels of this gene family (consisting, in mouse, of three active genes, Saa1, Saa2, Saa3) were 9-to 55-fold higher in old mice compared to young animals. These results suggest that inflammation is a component of aging process in the liver, according to the concept of the existence in aged animals of a state of chronic inflammation in the absence of Bstressors.^Genes involved in immune response were also up-regulated in aged liver; particularly striking was the 40-fold increase in the expression of lipocalin 2, a novel autocrine and paracrine adipokine, which acts as an antagonist of inflammatory molecules.…”
Section: Resultssupporting
confidence: 93%
“…Another marker of inflammation is Creactive protein (CRP), which is produced in the liver largely in response to elevations in IL-6. This general marker of inflammation is also elevated in older adults relative to young ones (Ballou et al, 1996). All of these specific changes put older individuals at an increased risk for the diseases mentioned above, including but not limited to cardiovascular disease.…”
Section: Age and Immune Functionmentioning
confidence: 97%
“…In addition to ECM accumulation, inflammation is a key component of cardiac aging (13,48). Higher levels of circulating proinflammatory cytokines are observed in elderly people, even in the absence of chronic disease (3,8,16,50). In old mice, the cardiac expression of inflammatory genes increases compared with that in young mice (56).…”
mentioning
confidence: 99%